The Effectiveness of Flipped Classroom Learning Model for Increasing Students’ Reading Comprehension in Covid-19 Pandemic - Miftahul Rachmat; Liliana Muliastuti; Ifan Iskandar (Basic and Applied Education Research Journal, 2021)
Since Covid-19 Pandemic hit Indonesia and the teaching learning in the classroom cannot be obtains and make unpleased teaching learning process, researcher used a flipped classroom learning model for teaching students’ reading comprehension as the solution. This model includes active learning; student involvement and modern technology by using ICT. In a flipped classroom, the material given through videos and Power Point via WhatsApp group and students watched in their homes before the virtual class is obtained. The objective of this research is to know the effectiveness of flipped classroom learning model for increasing students’ reading comprehension. The researcher took the samples from fourth semester students in extensive reading course from the English education department of UIN Sultan Maulana Hasanuddin Banten. After this experimental research process has been completed, this flipped classroom learning model increasing students' reading comprehension.